Cycle Tourism in Olt County, Romania. (Re)Discovering Potential of History and Geography for Tourism - Viorel Mionel; Oana Mionel (Amfiteatru Economic Journal, 2016)
Olt is among Romania's counties that remains hidden when it comes to tourism. Unlike other Romania's counties that possess tourism advantages in the form of landscape or anthropic heritage, Olt county appears to lack the first part. However, the landscape is developed on a wavy morphology with not so crowded roads that favours cyclotourism. Therefore, the analysis focused on highlighting the historical-geographic objectives with touristic potential, as well as turing them to good account in the form of cycle routes. The novelty of the research is to design four cycle routes using Strava app and choosing a county in the lowlands as a case study. At the time of this analysis cycle tourism in Olt county, there was only one route for cyclists, currently online, but without no touristic importance. The methodology used involved identifying historical and geographical ob jectives of national importance, structuring categories and grouping them into four mixed tracks which were dedicated to cyclists. Previous stages were followed by field research in order to collect technical data (map, time, distance, total ascent etc.). Finally, a critical review of proposed bicycle routes was undertaken in the research. Study results showed that cycling tourism is a real opportunity for Olt county economy thanks to the number and value of the present tourism potential objectives. Nevertheless, at this stage, the lack of infrastructure, promotion and the small number of units makes it difficult to organize cycle tourism. What is more, the lack of cycle paths endangers cyclotourists' safety.
Keywords: L83; Q57; Q58; R11; R14; 330; cycle tourism; Olt county; cycle routes; protected areas; cultural and historical objectives